Public Policies Reducing People at Risk of Poverty and Social Exclusion - Veleva, Ralica (Research Papers, 2018)
Reducing the people at risk of poverty and social exclusion is one of the major challenges facing both the European Union and Bulgaria. This article focuses on analyzing the programs and measures adopted at European, National, Regional, and Local levels to achieve the purposes. The main trends are outlined, and the article proposes a number of measures to reduce people at social exclusion. They are mainly related to: reducing early school leavers, enhancing qualifications and initiating a new educational cycle.
Keywords: People at risk of poverty; Social exclusion; Public policies